Mapping Career Options for Class XI MAN Blitar City Students - Nanda Istiqomah; Nur Yanah; Setyo Pranoto; Arildalona Ilhamawan Tarnasta (Institut Attanwir Bojonegoro, 2024)
Career choice mapping is part of the assessment in identifying student career choice tendencies. Counselors can use the results of this career choice mapping as a basis for providing career guidance services so that they suit student needs. The research aims to map the career choices of class XI MAN Blitar City students. The method used is the Holland career test using the RIASEC model (Realistic, Investigative, Artistic, Social, Enterprising, Conventional). The number of respondents was 187 students. The research results showed that 17% of respondents had realistic characters, 14% had Investigative characters, 15% had Artistic characters, 21% had Social characters, 16% had Enterprising characters, and 17% had Conventional characters. Based on the results of this research, it can be concluded that social characters dominate and investigative characters have the lowest value. The results of this research are an initial stage which can then be used as a basis for preparing a career guidance service program, bearing in mind that the service delivery process is carried out in stages and continuously.